Pengertian Ushul Fiqih dan Fiqih serta hubungan antar keduanya - Aliffiana, Bilqis (Maliki Interdisciplinary Journal, 2023)
In the context of Ushul Fiqh, the principles of interpretation of Islamic law sources such as the Al-Quran and Hadith are studied. The methods and approaches studied in Usul Fiqh provide a framework for Fiqh experts to interpret and derive laws from these sources. Meanwhile, Fiqh applies the principles and methodologies learned in Usul Fiqh in implementing Islamic laws in various aspects. life. , Usul Fiqh and Fiqh have a close relationship. Usul Fiqh provides the theoretical basis, methodology, and principles of interpretation, while Fiqh provides practical implementation in issuing Islamic laws. This relationship plays an important role in understanding, establishing and implementing Islamic laws in the daily life of Muslims